Surgical outcome of type I tympanoplasty in different types of mucosal chronic otitis media: a prospective study - Harkare, Vivek V.; Pidurkar, Shiwani S.; Khadakkar, Sonali P.; Deosthale, Nitin V.; Dhoke, Priti R.; Dhote, Kanchan S. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: Chronic otitis media (COM) is a long-standing infection of middle ear cleft, causes severe destruction and leading to irreversible sequelae. The interval to convert discharging ear into dry is variable. Extensive counselling is required to keep these patients motivated for prolonged treatment duration. Hence, the study was conducted. Methods: A prospective study was carried out at NKP Salve and Lata Mangeshkar Hospital Nagpur, Maharashtra, between the age group of 16-60 years, who underwent type 1 tympanoplasty. Results were statistically analysed with respect to graft uptake, hearing improvement and size of perforation over a period of 2 years. Temporalis fascia was taken as a graft material. Results: Out of 70 cases, 38 cases had inactive ears and 32 cases had minimal, mucoid ear discharge (Active ear), which bacteriologically showed no organism. M:F ratio was 1.12:1. Graft uptake was successful in 92.11% of the cases in inactive group and 93.75% of the cases in active group. Graft uptake was 100% in small and moderate perforation. Hearing improvement was achieved in 71.05% of cases in the inactive group and 78.12% of cases in the active group, as measured by closure of the air-bone gap (ABG) and improvement in conductive hearing (significant >10 dB). We found no difference in the success rates. Conclusions: Presence of minimal discharge will not affect the surgical outcome of type 1 tympanoplasty in terms of graft uptake, hearing improvement and size of perforation.